LEADERSHIP STYLE STRATEGY IN IMPROVING EMPLOYEE PERFORMANCE AT THE LAHEWA DISTRICT OFFICE NORTH NIAS REGENCY - Firman Lase; Odaligoziduhu Halawa; Eliagus Telaumbanua; Yamolala Zega (LPPM YPITI, 2026)
This study aims to analyze leadership style strategies in improving employee performance at the Lahewa District Office, North Nias Regency. The focus of this study covers three main things: (1) to determine the leadership style strategies applied at the Lahewa District Office in improving employee performance, (2) to determine the obstacles faced in implementing these leadership style strategies, and (3) to identify strategies that can be applied to improve leadership effectiveness in an effort to improve employee performance. This study uses a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results of the study indicate that the dominant leadership style applied at the Lahewa District Office is a participatory leadership style, where leaders involve employees in decision-making and provide space for employees to express ideas and input. However, in its implementation, several obstacles were found, such as a lack of effective communication between leaders and employees, low motivation of some employees, and limited work support facilities. To overcome these obstacles, strategies that can be applied include increasing the intensity of communication, providing periodic self-development training, and providing adequate facilities and infrastructure to support the implementation of tasks. Through the implementation of these strategies, leadership effectiveness is expected to increase, thus having a positive impact on improving employee performance.